Grandmaster of demonic cultivation, the comic = Mo dao zu shi. 4 - Moxiangtongxiu (Seven Seas Entertainment, 2023)
"Lan Wangji and Wei Wuxian arrive at a desolate city where the bodies of massacred clan members rest uneasily in their graves. A cold case here once shocked the major cultivation clans-and the murderer may still be at large. But to rescue the junior clan members trapped in the city, the two men must battle their way through fierce corpses that Wei Wuxian can't control. Who created this ghost town in the first place, defying the edict of the founder of demonic cultivation? A mysterious blind ghost may carry the answers."--Publisher description.